Kecernaan In Vitro Komponen Serat Ransum Ternak Sapi yang Menggunakan Kulit Buah Jagung Amoniasi - Andayani, Jul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
An experiment was conducted to evaluate in vitro digestibility of  fiber components of the cattle ration containing ammoniated  corn husk.  Parameters measured in the present experiment were   Dry Matter (DM), Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF) in vitro digestibilities.  This  study  was  assigned  into  completely  randomized  design  (CRD)  with  5  treatments  and  4 replications. The treatments were ; T0 = 70% Forage (100% grass + 0% ammoniated Corn husk) + 30 % Concentrate,  T1 = 70% Forage (75 % grass + 25% ammoniated Corn husk) + 30 % Concentrate, T2 = 70% Forage (50% grass + 50% ammoniated Corn husk) + 30 % Concentrate, T3 = 70% Forage (25% grass  +  75%  ammoniated  Corn  husk)  +  30  %  Concentrate,  T4  =  70%  Forage  (0%  grass  +  100% ammoniated Corn husk) + 30 % Concentrate.   Results of this study showed that the treatments were significantly (P<0,05) influence of dry matter, NDF and ADF digestibilities.  Increasing percentage of  corn husk ammoniation in the ration increased in vitro digestibility. It is concluded that ammoniation with urea to corn husk could  increase digestibility and the ammoniated corn husk  ammoniation may substitude forage for cattle ration.